The Influence of Job Involvement and Career Development on the Work Motivation of Civil Servants in the Cooperative, Small and Medium Enterprises Department of West Kalimantan Province - Puput Rahmawati; Eru Ahmadia (Electronic Journal of Education, Social Economics and Technology, 2025)
This study examines the impact of Job Involvement and Career Development on Work Motivation among civil servants at the Cooperative, Small and Medium Enterprises Department of West Kalimantan Province. Using an associative research approach, primary data was collected through interviews and questionnaires distributed to 51 civil servants working in this department. The findings reveal that both Job Involvement and Career Development have a positive and significant impact on Work Motivation. The F-test results show that Job Involvement and Career Development simultaneously have a significant effect on Work Motivation (F = 26.465, p 0.05). Additionally, the t-test results confirm that both variables significantly influence Work Motivation on a partial basis: Job Involvement (t = 4.097, p 0.05) and Career Development (t = 2.179, p 0.05). These findings indicate that increasing employee involvement in their work and providing clear career development opportunities are crucial strategies for enhancing motivation, reducing absenteeism, and driving higher performance. The study also suggests that when employees perceive clear and meaningful career prospects within their organization, they are more likely to be motivated, engaged, and committed to their roles. These insights offer valuable guidance for human resource management, especially within public sector institutions, and emphasize the importance of creating a work environment that fosters growth, motivation, and long-term employee satisfaction.